Uncovering the extent of dementia prevalence in Iran: a comprehensive systematic review and meta-analysis - Sima Oshnouei; Mahin Safaralizade; Nazila Farrokh Eslamlou; Mohammad Heidari (BMC, 2024)
Abstract Background Dementia is one of the major causes of disability and dependency among older people worldwide. The formation of an aging population in Iran can be associated with societal problems, including age-related disorders such as dementia. This study aimed to estimate the prevalence of dementia& Alzheimer disease in adults aged 60 years or older and it's its geographical distribution in Iran. Methods A systematic review and meta-analysis study included articles published in both English and Persian languages and utilized various databases including: Google Scholar, PubMed, Web of Science, Magiran, and thesis database of medicine universities up to December 2022. The pooled prevalence was calculated using random effects models. The prevalence was reported separately for different geographical locations and types of area sampling, and age adjustment was performed for the selected studies. All statistical analyses were conducted using metaprop package in STATA version 17. The I2 statistic was applied to assess heterogeneity. Results The meta-analysis considered nine relevant studies that were carried out up to 2023 in Iran. The study found that the prevalence of dementia in central and east counties was estimated to be 0.14 (95% CI; 0.04-0.31), while in western counties, the prevalence was estimated to be 0.1 (95%CI; 0.01-0.27). The estimated overall crude prevalence of dementia was estimated at 0.14 (95% CI; 0.03-0.31). Estimated prevalence-based health centers sampling and hospital-based studies were 0.02 (95% CI; 0.02-0.03), 0.05 (95% CI 0.06-0.11), respectively. One study used nursing home sampling as the sampling method, and the estimated prevalence was 0.43 (95%CI 0.38-0.49). Conclusion This is the first systematic review and meta-analysis of the prevalence of dementia's disease up to 2023 in Iran. The estimated overall prevalence of dementia is lower than the reported prevalence in European countries and similar to other Asian countries.